OATH IN THE HISTORY OF SERBIAN CONSTITUTIONALISM - Pavlović, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Abstract: The article deals with oaths in constitutions of Principality and Kingdom of Serbia, of Kingdom of SHS/Yugoslavia, of Yugoslav communist’s constitutions and of post communist’s constitutional of Republic of Serbia. In constitutions of Principality and Kingdom of Serbia, oaths were religious. Oaths in St. Vitus Constitution were religious also. However, in debates during creation this Constitution, there were many arguments against religious oath, but in favor of nonreligious affirmations. In the September Constitution (1931), the oath of representatives was nonreligious. In communist constitution the oaths were made according to yugoslav communist ideology. In post-communist constitutions the oaths were shaped according to ideology of human rights. In some situations oath was given an exceptional importance. Firstly (1859), the oath of counsellors was the first step in building independent state; secondly (1920/21), the representative’s oath had the purpose to save monarchy; thirdly, presidential oath in last Serbian Constitution (2006) was as important as guard of part of state’s territory (Kosovo i Metohija).